Affinity chromatography and inhibition of chorismate mutase-prephenate dehydrogenase by derivatives of phenylalanine and tyrosine. - Smith, G D (1977)
Several derivatives of phenylalanine and tyrosine were prepared and tested for inhibition of chorismate mutase-prephenate dehydrogenase (EC 1.3.1.12) from Escherichia coli K12 (strain JP 232). The best inhibitors were N-toluene-p-sulphonyl-L-phenylalanine, N-benzenesulphonyl-L-phenylalanine and N-benzloxycarbonyl-L-phenylalanine. Consequently two compounds, N-toluene-sulphonyl-L-p-aminophenylalanine and N-p-aminobenzenesulphonyl-L-phenylalanine, were synthesized for coupling to CNBr-activated Sepharose-4B. The N-toluene-p-sulphonyl-L-p-aminophenylalanine-Sepharose-4B conjugate was shown to bind the enzyme very strongly at pH 7.5. The enzyme was not eluted by various eluents, including 1 M-NaCl, but could be quantitatively recovered by washing with buffer of pH9. Elution was more effective in the presence of 10 mM-1-adamantaneacetic acid, a competitive inhibitor of the enzyme. This affinity-chromatography procedure results in a high degree of purification of the enzyme and can be used to prepare the enzyme in a one-step procedure from the bacterial crude extract. Such a procedure may therefore prove useful in studying this enzyme in a state that closely resembles that in vivo.